Perceived competence and impression management: Testing the mediating and moderating mechanisms. (18th July 2018) - Abbas, Muhammad; Raja, Usman; Anjum, Mansoor; Bouckenooghe, Dave
Abstract : Using a diverse and unique sample of triads ( N = 191 self, peer, and supervisor reports) from a field survey of two service sector organisations, this study examined the effects of perceived competence (self‐reported) and supervisor‐rated performance ratings on peer‐rated impression management. The study also tested the mediating role of performance in competence–impression management relationships and the moderating role of job satisfaction (self‐reported) in performance–impression management relationships using bootstrapping techniques. The study further examined the conditional indirect effects (i.e., moderated mediation) of perceived competence on impression management. The sample consisted of white collar employees from a government organisation and a leading cellular company in a developing country (i.e., Pakistan). Employees with low perceived competence were more likely to use impression management tactics than were those with high perceived competence. Similarly, poor performance ratings produced high impression management. Moreover, performance mediated the relationship between competence and impression management. The findings also suggest that perceived competence has a negative indirect effect on impression management for those with high levels of job satisfaction. Finally, impression management was highest when performance and satisfaction were low.